Laparoscopic Pancreaticoduodenectomy in Elderly Patients: Systematic Review and Meta-Analysis - Wang, Qiang; Chen, Chengxin; Li, Haiyang (Frontiers in Surgery, 2022)
Background: The safety and efficacy of Laparoscopic pancreaticoduodenectomy (LPD) in elderly patients who often suffer from pre-existing conditions (e.g., cardiovascular diseases) and poor functional reserve remain unclear. This meta-analysis aimed to evaluate the safety and efficacy of LPD in elderly patients. Methods: A systematic literature search was conducted using the PubMed, Embase, Web of Science, and Cochrane Library databases. All studies published from their inception to January 2022 reporting perioperative outcomes after LPD in elderly patients were included in the search (Group 1, comparing the perioperative outcomes of LPD and OPD in elderly patients; Group 2, comparing the perioperative outcomes after LPD between elderly and non-elderly patients). The evaluated outcomes included perioperative mortality, postoperative complications, conversion, operative time, estimated blood loss (EBL), postoperative hospital stay (POHS), and readmission. Results: In total 8 studies were included in the meta-analysis. Pooled analysis of Group 1 showed that EBL, 90-day mortality, major morbidity, bile leak, POH, abdominal infection, reoperation, POP, POCE, and readmission were not significantly different between the LPD and the OPD group. LPD was associated with longer operative time, lower POPF rate, lower DEG rate, and shorter POHS. Pooled analysis of Group 2 showed that mortality, major morbidity, POPF, DEG, bile leak, POH, abdominal infection, reoperation, conversion, operative time, EBL, and readmission were not significantly different between the elderly and the non-elderly group. The POHS of elderly group was significantly longer than non-elderly group. Conclusion: LPD may be a safe and feasible procedure for elderly patients and is associated with short POHS.